Pembelajaran Berbasis Kearifan Lokal di Masa Pandemi Dalam Konteks Eksistensi dan Kreativitas Guru - Bambang Parmadi; Ogy Agiustora; Wembrayarli Wembrayarli; Feri Noperman (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
Elementary school educators and AUD have an important role to improve the various abilities of children, especially in the golden age of children. The teacher himself maximizes the golden age phase which falls at the age of kindergarten using various teaching methods and involves parents in designing early childhood learning. The purpose of this study was to describe the role of teachers in designing local wisdom-based learning in Elementary Schools and Early Childhood Education in Bengkulu City. This study used descriptive qualitative methods. Research data were collected through observation, interviews and documentation and then analyzed using data reduction, data presentation, conclusion drawing and verification. The results showed that the preparation of learning based on local wisdom was carried out by noting the potential that existed in the surrounding environment, including the environmental conditions of the community, customs prevailing in the community, the language used, folk songs, special foods, local handicrafts and traditional games. In addition, it is carried out based on experiences carried out in Elementary Schools and PAUD in Bengkulu City and arranged based on the elements needed in a learning management, then integrated with the need for the introduction of local culture to students and love of local culture.